PENEGAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PERJUDIAN MELALUI GAME ONLINE YANG MENGGUNAKAN SISTEM GACHA - Darmawan Abdullah; Karolus Kopong Medan; Deddy R.Ch Manafe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Gambling has increasingly appeared in disguised forms through the gacha system in online games, causing addiction, financial losses, and secondary criminality, particularly among youth. Indonesian criminal law, however, remains ambiguous in classifying this practice as gambling. This study addresses two questions: (1) Can online games using gacha be considered criminal gambling under Indonesian law? (2) How is law enforcement implemented against such gambling? Using a normative legal methodology with statutory and conceptual approaches, the study examines primary sources (Law No. 1 of 2023 on the National Criminal Code, Law No. 1 of 2024 on Electronic Information and Transactions, and Minister of Communication and Informatics Regulation No. 2 of 2024), as well as secondary and tertiary materials, analyzed descriptively and qualitatively. Findings indicate that: (1) The gacha system qualifies as criminal gambling because it involves a game, chance, and wagering, especially with Real Money Trade (RMT) converting virtual items into real currency, in line with Articles 426–427 of the National Criminal Code, Article 27(2) of the Electronic Information and Transactions Law, and the classification of “simulation and/or gambling activities” in the Ministerial Regulation. (2) Law enforcement employs both penal and non-penal strategies, including legislation, police investigation, access blocking by the Ministry, and administrative or criminal sanctions, though hindered by extraterritorial jurisdiction, complex digital evidence, and lack of specific regulations. To ensure effective deterrence, adaptive regulations, international cooperation, and public education are essential to mitigate the negative impacts of digital gambling.